Typing the Minority Tai Languages in the Internet World: Transnational Communication and Language Maintenance through the Tai Tham Keyboard - Dao, Sirui (The Journal of the Siam Society, 2022)
In the age of the nation-state, many minority languages face the danger of disappearance, including some minority Tai languages. The Tham script was once widely used in written communication by these minority Tai speakers in Northern Thailand, the Eastern Shan State of Myanmar, and Yunnan province of China. In the 20th century, the domains of these languages and the script shrank. However, electronic technology seems to have revived this centuries-old script and the minority languages it transliterates. In 2009, encoding into the Unicode Standard realized trans-platform communication with the Tham script. In 2013, a monk from Chiang Tung (Myanmar) released a Unicode Tham input method, named Tai Tham (UN) Keyboard. By mid-2015, assisted by Tai people in Thailand and China, this input method was applied to both computer and mobile devices. Its development, maintenance and distribution witness the trans-border ethnic connection between Tai peoples in Myanmar, Thailand and China. The use of the Tai Tham Keyboard in an unbounded internet world seems to contribute to the language maintenance of these minority Tai languages. However, many obstacles (complexity of keyboard layout, conflict of the font display, censorship, lack of daily usage support, and problems of language competence) hinder its function. By employing the methods of survey, in-depth interview and participant observation, this article studies the trans-border connection in the processes of its development and distribution, its usage and shortcomings in different contexts.